2020
DOI: 10.1038/s41597-020-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

A dataset of multi-functional ecological traits of Brazilian bees

Abstract: that explain bee community structure include body size, flight range, sociality, nesting location, nest behavior and diet 29,34,35. Here, we compiled a dataset of bee species from the Brazilian iron-rich mountains located in the Amazon (Pará State) and Atlantic Forest (Minas Gerais State). The dataset contains records of bees collected from 1983 to 2018 but in disconnected time frames. It represents one of the most comprehensive and robust datasets of bee species from Brazil and a unique dataset of bee species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…These distances represent half the flight capacity estimated for M. fasciculata using the same equipment as the present study and in the same environment (Nunes-Silva et al 2019). Melipona seminigra has a body size approximately 2 mm smaller than M. fasciculata (Costa 2019), and the intertegular distance of M. seminigra is 2.9 mm, 0.4 mm smaller than the 3.3 mm of M. fasciculata (Borges et al 2020). Thus, this result corroborates previous studies that show a correlation between body size and flight capacity of Meliponini species (Araújo et al 2004;Greenleaf et al 2007;Mayes et al 2019;Nieuwstadt and Iraheta 1996).…”
Section: Discussionsupporting
confidence: 52%
“…These distances represent half the flight capacity estimated for M. fasciculata using the same equipment as the present study and in the same environment (Nunes-Silva et al 2019). Melipona seminigra has a body size approximately 2 mm smaller than M. fasciculata (Costa 2019), and the intertegular distance of M. seminigra is 2.9 mm, 0.4 mm smaller than the 3.3 mm of M. fasciculata (Borges et al 2020). Thus, this result corroborates previous studies that show a correlation between body size and flight capacity of Meliponini species (Araújo et al 2004;Greenleaf et al 2007;Mayes et al 2019;Nieuwstadt and Iraheta 1996).…”
Section: Discussionsupporting
confidence: 52%
“…Public policies for pollinator conservation have already been suggested, being particularly important for the conservation of natural areas near or within crops (Garibaldi et al 2014 ). This is particularly important for açaí, a crop mainly pollinated by small stingless bees (such as small Trigona -like bees, Campbell et al 2018 ), with short flight ranges and more commonly found on well-preserved habitats, due to their nesting requirements (Borges et al 2020 ); in fact, crops near forested areas presented higher fruit production (Campbell et al 2018 ). In this sense, conservation of legal reserves and maintenance of forest patches within rural areas is a particularly important mechanism in Brazil for the conservation and sustainable use of biodiversity (Garibaldi et al 2011 , Metzger et al 2019 ), which should be encouraged and regulated, especially in the Amazon biome states (Freitas et al 2015 , Christmann 2019 , Metzger et al 2019 , Nunes et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, elas contribuem ativamente na recuperação de ecossistemas degradados [Giannini et al 2020], podem ser utilizadas em biovetorização, tecnologia que envolve o uso de insetos como agentes de biocontrole [Macharia et al 2020] e também podem desempenhar um papel crucial em projetos e programas de desenvolvimento sustentável [Giannini et al 2020]. Perdas de biodiversidade entre abelhas nativas têm sido documentadas para as regiões tropicais [Sánchez-bayo e WyckhuysBorges 2019] e [Borges et al 2020]. Os principais fatores responsáveis por esse declínio incluem: infecções disseminadas por parasitas e patógenos; falta de variabilidade genética; estresse devido a movimentação sazonal de colmeias para polinização de frutas e hortaliças; resíduos de pesticidas tóxicos encontrados no pólen e néctar ou aplicado a colmeias para controlar ácaros; baixo valor nutricional de agropaisagens dominadas por monoculturas (como milho, soja e algodão); e condições climáticas mais adversas das últimas décadas [Hallmann et al 2017], [Sánchez-bayo e WyckhuysBorges 2019], [Gomes et al 2020], [Filipiak 2018] e [Marstaller et al 2019].…”
Section: Introductionunclassified